2020
DOI: 10.3390/cosmetics7020038
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Bacterial Spoilage in Cosmetics by a New Bioanalytical Approach: API-SPME-GC-MS to Monitor MVOCs

Abstract: The main goal of this work was the use of the powerful solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) technique to unequivocally identify microbial volatile organic compounds (MVOCs) derived from the enzymatic activity produced during metabolic processes using analytical profile index (API) biochemical tests. Three bacteria were selected for this study: Escherichia coli, Proteus mirabilis, and Pseudomonas aeruginosa. They were inoculated and incubated to both API components and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Beyond nail products, the use of API-SPME-GC-MS for the identification of microbial presence in cosmetics through microbial volatile organic compounds (MVOC) has recently been reported. These MVOCs, derived from enzymatic activity produced during metabolic processes, serve as biomarkers for the identification of studied bacteria, such as the following: Indole and 2-nitrophenol for Escherichia coli, 2-undecanone and phenylethyl alcohol for Proteus mirabilis, 1-undecene and 2 -aminoacetophenone for Pseudomonas aeruginosa., and at least three other MVOCs as general indicators of bacterial presence [71]. This analysis concluded that the use of SPME-GC-MS is a fast, robust, and highly valuable tool that complements API biochemical tests in the assessment of microbial contamination in cosmetics [71].…”
Section: Gas Chromatographymentioning
confidence: 97%
“…Beyond nail products, the use of API-SPME-GC-MS for the identification of microbial presence in cosmetics through microbial volatile organic compounds (MVOC) has recently been reported. These MVOCs, derived from enzymatic activity produced during metabolic processes, serve as biomarkers for the identification of studied bacteria, such as the following: Indole and 2-nitrophenol for Escherichia coli, 2-undecanone and phenylethyl alcohol for Proteus mirabilis, 1-undecene and 2 -aminoacetophenone for Pseudomonas aeruginosa., and at least three other MVOCs as general indicators of bacterial presence [71]. This analysis concluded that the use of SPME-GC-MS is a fast, robust, and highly valuable tool that complements API biochemical tests in the assessment of microbial contamination in cosmetics [71].…”
Section: Gas Chromatographymentioning
confidence: 97%
“…It is well known that bacteria produce microbial volatile organic compounds (MVOCs), which are formed during bacterial metabolic processes. This way, SPME employing commercial PDMS/DVB/CAR fibres has been employed to perform an in situ extraction and preconcentration of the MVOCs in a single step [ 133 , 134 ]. Afterwards, GC-MS has been employed as determination technique to unequivocally identify the MVOCs derived from the enzymatic activity, allowing the identification of several of them as specific markers for each one of the studied bacteria, as well as others as general indicators of bacteria presence.…”
Section: Sample Preparation Strategies For Cosmetics Analysismentioning
confidence: 99%
“…In this context, direct epifluorescence filter techniques (DEFT) and bioluminescence ATP, next to modern molecular approaches using genomic and proteomic information, are increasingly being advocated as promising alternatives. The latter comprises polymerase chain reaction (PCR), quantitative PCR (qPCR), digital PCR (dPCR), high-throughput next-generation DNA sequencing, matrix-assisted laser desorption ionization-time-of-flight (MALDI-TOF) MS, ion mobility spectrometry (IMS) or determination of biomarker volatile organic compounds (MVOC) by solid-phase microextraction gas chromatography-mass spectrometry [5][6][7][8][9]. Matching with cultureindependent methods, we succeeded in employing qPCR and most-probable number techniques for detecting paint-spoiling bacteria in general and sulfate-reducing bacteria in particular in a previous investigation [10].…”
Section: Introductionmentioning
confidence: 99%